Genetic characterization of the rabies virus strain QR 18867 (Rhabdoviridae, Lyssavirus) isolated from the uroderma Bilomatum Bat in Portel municipality, Pará State, 2004 - Nunes, Keley Nascimento Barbosa (2008)
Trabalho apresentado na Annual Meeting ASTMH, 57., 2008, New Orleans (LA)